2009
DOI: 10.1063/1.3211130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thickness on the cation segregation in epitaxial (001) and (110) La2/3Ca1/3MnO3 thin films

Abstract: Electron-energy-loss spectroscopy is used to map composition and electronic states in epitaxial La 2/3 Ca 1/3 MnO 3 ͑LCMO͒ films of various thicknesses grown on SrTiO 3 ͑001͒ and ͑110͒ substrates. For relatively thick films ͑Ն20 nm͒, epitaxial tensile strain in ͑001͒ films promotes a compositional La/Ca gradient across the film thickness, being the interface La rich, while the relaxed ͑110͒ films are chemically homogeneous. In contrast, much thinner ͑001͒ and ͑110͒ LCMO films display a different La/Ca distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 15 publications
3
36
0
1
Order By: Relevance
“…This deviation points to a slight oxygen deficiency in these films 55,56 and is attributed to the beneficial effect of the formation of oxygen vacancies in order to reduce the lattice mismatch for films which grow under tensile lattice strain. 57 Partially relaxed films on ReScO 3 with Re 5 Dy, Tb, Gd PFM data in Figs. 5(a)-5(c) show that domain formation critically depends on the magnitude of lattice mismatch.…”
Section: Partially Relaxed Films On Ndgaomentioning
confidence: 99%
“…This deviation points to a slight oxygen deficiency in these films 55,56 and is attributed to the beneficial effect of the formation of oxygen vacancies in order to reduce the lattice mismatch for films which grow under tensile lattice strain. 57 Partially relaxed films on ReScO 3 with Re 5 Dy, Tb, Gd PFM data in Figs. 5(a)-5(c) show that domain formation critically depends on the magnitude of lattice mismatch.…”
Section: Partially Relaxed Films On Ndgaomentioning
confidence: 99%
“…40, 41 An increase in Fe content may make it easier to equilibrate a larger amount of (positively charged) oxygen vacancies near the surface that electrostatically prefers Sr 2+ ions more than the Ti 4+ or Fe 3+/4+ ions. Second is the elastic interactions related to large size of Sr, which can drive the Sr to 20 free surfaces to minimize the elastic energy of the system 42,43 (note that the lattice parameter of STF decreases with increasing Fe content 18 ). In the authors' ongoing research, these driving forces for cation segregation phenomenon are being assessed quantitatively using both experiments and computation.…”
Section: Surface Chemical Composition and The Binding Environment Of Srmentioning
confidence: 99%
“…In our recent work, we showed that cation segregation can be described by the elastic and electrostatic interactions of the dopant with the surrounding lattice in perovskite oxides. (1) The specific mechanisms include the size mismatch between the dopant and host cations and the associated elastic energy minimization by pushing the dopant to free surfaces or interfaces (18)(19)(20)(21), and the charged defect interactions, such as a strong association of dopant cations with oxygen vacancies, which can drive the dopants to positively charged interfaces where oxygen vacancies are in abundance (22) as well as with polar surfaces. Based on this understanding, we propose that deficiency of the A-site cations on the perovskite lattice should suppress the dopant segregation on the A-site by allowing for more space in the bulk and reducing the elastic energy.…”
Section: Introductionmentioning
confidence: 99%